Systematic morphological characterization of sub-visible particles generated from cardiovascular devices using dynamic image analysis - Kurzhals Anja (Current Directions in Biomedical Engineering, 2021)
The assessment of particulate matter generated during a simulated use is requested by international standards for approval of cardiovascular devices. The particle suspension was generated during a simulated use test procedure of a commercially available coronary stent delivery system and analyzed by Dynamic image analysis (DIA) using FlowCAM 8000. Four parameters were analyzed: the diameter, the aspect ratio value, the circularity and the intensity. The results revealed that 53% of the particles were larger than 25 μm. The particle shapes were inhomogeneous with a wide ranging aspect ratio of 0.03 to 0.95. Around 83% had an intensity value of more than 140 grey scales and appeared translucent.